Diurnal Changes in Active Carbon and Nitrogen Pathways Along the Temperature Gradient in Porcelana Hot Spring Microbial Mat - Alcamán-Arias, María E.; Pedrós-Alió, Carlos; Tamames, Javier; Fernández, Camila; Pérez-Pantoja, Danilo; Vásquez, Mónica; Díez, Beatriz (Frontiers in microbiology, 2018)
Composition, carbon and nitrogen uptake, and gene transcription of microbial mat communities in Porcelana neutral hot spring (Northern Chilean Patagonia) were analyzed using metagenomics, metatranscriptomics and isotopically labeled carbon (H CO ) and nitrogen ( NH Cl and K NO ) assimilation rates. The microbial mat community included 31 phyla, of which only and were dominant. At 58°C both phyla co-occurred, with similar contributions in relative abundances in metagenomes and total transcriptional activity. At 66°C, filamentous anoxygenic phototrophic were >90% responsible for the total transcriptional activity recovered, while contributed most metagenomics and metatranscriptomics reads at 48°C. According to such reads, phototrophy was carried out both through oxygenic photosynthesis by (mostly ) and anoxygenic phototrophy due mainly to . Inorganic carbon assimilation through the Calvin-Benson cycle was almost exclusively due to , which was the main primary producer at lower temperatures. Two other CO fixation pathways were active at certain times and temperatures as indicated by transcripts: 3-hydroxypropionate (3-HP) bi-cycle due to and 3-hydroxypropionate-4-hydroxybutyrate (HH) cycle carried out by . The active transcription of the genes involved in these C-fixation pathways correlated with high determined carbon fixation rates. measurements of ammonia assimilation and nitrogen fixation (exclusively attributed to and mostly to sp.) showed these were the most important nitrogen acquisition pathways at 58 and 48°C. At 66°C ammonia oxidation genes were actively transcribed (mostly due to ). Reads indicated that denitrification was present as a nitrogen sink at all temperatures and that dissimilatory nitrate reduction to ammonia (DNRA) contributed very little. The combination of metagenomic and metatranscriptomic analysis with assimilation rates, allowed the reconstruction of day and night carbon and nitrogen assimilation pathways together with the contribution of keystone microorganisms in this natural hot spring microbial mat.